Cuidados de enfermagem à pessoa idosa indígena com hipertensão arterial da atenção primária: revisão de escopo - Lima, Alexia Victoria Barbosa de (Brasil, 2025)
Introduction: The indigenous population faces specific health challenges due to the difficult access and devaluation of their cultural knowledge. Nursing has a vital role in the prevention and control of these conditions in indigenous elderly, integrating cultural knowledge in order to improve adherence to treatment. Objective: To map scientific evidence on nursing care for indigenous elderly people with hypertension on the world stage. Method: This is a scope review guided by the guidelines of the Joanna Briggs Institute (JBI). The research used the mnemonic PCC (Population: hypertensive indigenous elderly person; Concept: nursing care; Context: worldwide) and was developed in five stages: 1) Identification of the research question, formulating the guiding question; 2) Research strategy, using DeCS/MeSH and Emtree descriptors, with database searches and gray literature; 3) Screening and selection of sources, conducted with the help of Rayyan software and inclusion criteria; 4) Data extraction, using an adapted instrument based on the JBI model; and 5) Analysis and presentation of the results, organized into themes and presented in a narrative and descriptive way, with comparisons based on the NIC. Results: Three studies on nursing interventions in indigenous populations with hypertension made up the review, they ranged from community and educational care to spiritual support. "Health Education" was a recurring intervention, highlighting the importance of culturally sensitive approaches in the management of indigenous hypertension. Conclusion: Indigenous health still faces gaps in the literature, especially related to nursing care focused on the assistance of this population, also presents a shortage in studies focused on the theme of the indigenous elderly.